ALERTA : KOTAK OBAT PINTAR BERBASIS IOMT UNTUK PENINGKATAN KEPATUHAN PASIEN TUBERKULOSIS - Shafa Salsabila Ramadhani; Muhammad Zulham Kentji; Moch. Fathoni Taufikur Rohim; Rafi Fulvian Fahri; Naufan Izzan Ath Thariq; Muhammad Ihsan Hafizh (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The spread and mortality rate of Tuberculosis (TB) in Indonesia remains high. Successful treatment depends heavily on patient compliance in taking Anti-Tuberculosis Drugs (OAT). This treatment requires patients to take the medication regularly for at least six months. Manual monitoring of Directly Observed Therapy Short Course (DOTS) has limitations. The limitations of patient monitoring systems encourage the development of effective remote monitoring technology. Therefore, this study designed ALERTA is a smart medicine box based on the Internet of Medical Things (IoMT) to optimize patient monitoring. This system is controlled by an ESP32 microcontroller integrated with a Hall effect sensor to detect opening and closing of the medicine box, and a DHT22 sensor to monitor the temperature and humidity of the storage room. To ensure punctuality, medication schedules are managed through a Real-Time Clock (RTC) module that sends real-time alerts to the dashboard and notifications. All data is directly integrated with the server so that patient compliance history can be objectively recorded. Through a series of tests, the hardware and software functions have been proven to work well. Implementation of this system has the potential to increase the effectiveness of TB treatment in Indonesia.